Efektivitas Bangunan Organic Coastal Defence (OCD) untuk Meningkatkan Persentase Keberhasilan Penanaman Mangrove di Mempawah Mangrove Park - Permanus, Trimei; Utomo, Kiki Prio; Jumiati, Jumiati (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
Damage to the mangrove forest ecosystem causes the erosion of beach-forming sediments. Mempawah Mangrove Park (MMP) has experienced severe abrasion and this abrasion caused the land around the coast of MMP to be lost in the current. The loss of land was exacerbated by the destruction of mangrove forests, so in 2011 MMP carried out reforestation of mangrove forests to restore the lost land. Planting often fails, where newly planted mangroves die and are lost in sea currents after 1 to 2 months after planting. In 2022 MMP will collaborate with Environmental Engineering Students at Tanjungpura University under the auspices of the Tanjungpura University Laboratory UPT in activities Matching fund to innovate mud-retaining buildings and breakwaters. The building was named Organic Coastal Defence (OCD). The OCD building consists of a mud retaining building (mud trap) and breakwater buildings (breakwater). The materials used are pieces of board, pieces of wood and pieces of bamboo, where the majority of these materials are left over from building construction in MMP. This building was proven to be able to increase the percentage of success in mangrove planting where during the 6 month monitoring period mangroves that were living in good condition reached 50% in mud trap 1 and 58%. on mud trap 2.